2016
DOI: 10.1177/1049732315601666
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Obsessive-Compulsive Disorder

Abstract: Obsessive-compulsive disorder (OCD) is a mental health problem characterized by persistent obsessions and compulsions. This article provides insights into experiences of OCD through a qualitative, thematic analysis performed upon a set of interviews with people with OCD. Four themes were found as central in the participants' descriptions of OCD episodes: 1) space, 2) the body, 3) objects and 4) interactions. The findings also show that episodes of OCD can be grouped into three broad categories: 1) activity epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 37 publications
(69 reference statements)
2
14
0
Order By: Relevance
“…Consistent with some quantitative [ 53 , 54 ] and qualitative work [ 11 , 13 , 17 ], several participants commented on the impact of their OCD on attendance and performance at school/university, and/or work. In their study with nine British individuals living with OCD, the authors identified the theme of ‘Failing at life’ and described this as the overwhelming impact of the disorder on education and careers [ 13 ].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Consistent with some quantitative [ 53 , 54 ] and qualitative work [ 11 , 13 , 17 ], several participants commented on the impact of their OCD on attendance and performance at school/university, and/or work. In their study with nine British individuals living with OCD, the authors identified the theme of ‘Failing at life’ and described this as the overwhelming impact of the disorder on education and careers [ 13 ].…”
Section: Discussionsupporting
confidence: 66%
“…Our study is part of a growing body of qualitative literature on OCD using exploratory approaches to better understand the perspectives of individuals living with OCD [ 11 13 , 15 , 17 ]. In her paper, Knapton [ 11 ] argues that the majority of studies on OCD are quantitative in nature and that our understanding of OCD, “has largely come from participants’ judgments of pre-defined and inflexible statements rather than from extended and unrestricted descriptions”, and that this approach limits, “intra-participant variation” (p. 2). In the current study, the findings provide instances of consistent and contrasting accounts of the experience of OCD—highlighting the heterogeneity of the disorder, and the importance of exploring individual perspectives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The participants' scores are then analyzed statistically and subtypes are posited based on the clustering of various symptoms (e.g., Calamari et al, 2004 ). While these methods have shed some light on subtypes of OCD, it is also possible to investigate subtypes through qualitative approaches (e.g., Knapton, 2015 ;Van Schalkwyk, Bhalla, Griepp, Kelmendi, Davidson, & Pittenger, 2015). Collecting open-ended accounts of OCD experiences through interviews or writing samples allows participants to describe OCD in their own words without forcing their experiences to fi t infl exible statements (Van Schalkwyk et al, 2015 ).…”
Section: Backg Roundmentioning
confidence: 99%